Oral Finasteride (5 mg and 2 mg) versus Topical Minoxidil 5% in Female Pattern Hair Loss - Eman Hamed El Morsy; Asmaa Saad Abd Toto; Eman Mohamed Hassan (Clinical Dermatology Review)
Background: Female pattern hair loss (FPHL) has a negative psychological and social impact. Lacks of consensus for its treatment as well as inconsistent response to treatment modalities are considered major challenges for physicians. Objectives: To assess the safety and efficacy of oral finasteride 5 mg and 2 mg versus topical minoxidil 5% in FPHL both clinically and by trichoscopy. Patients and Methods: Forty-five females with FPHL were included in the study for 6-month duration. Fifteen patients in Group A received oral finasteride 5 mg daily, 15 patients in Group B received oral finasteride 2 mg daily, and 15 patients in Group C were treated with topical minoxidil 5% solution. Assessment was done using Sinclair scale, photography, trichoscopy, degree of improvement, and patient satisfaction scale. Results: Significant improvement of Sinclair scale, hair density, and yellow dots in each group was noted along the treatment period; however, no further improvement of hair density in Group B after the 3rd month was detected. There was significant higher improvement in the hair density in Group A and C than Group B. The degree of improvement and patient satisfaction were significantly greater in Group A and C than Group B. A negative correlation between degree of improvement and patient’s age was observed in Group B. Conclusion: Oral finasteride 5 mg and topical minoxidil 5% gave comparable results in FPHL, yet both provided greater and maintained response than 2 mg finasteride. In addition, low-dose finasteride gave better responses in the younger age group. However, all three treatment options were safe in the treatment of FPHL.